2020
DOI: 10.1186/s40623-020-01258-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of terrestrial and Martian TEC at dawn and dusk during solstices

Abstract: This paper used the similarities between the ionospheres on Mars and Earth, the most similar of the terrestrial planets, to examine the relative importance of photochemical and transport processes at dawn and dusk. The amount of plasma present in the ionosphere, as measured by the total electron content (TEC), was examined at different locations for both solstice seasons over a solar cycle. Using the rate of change of TEC as a function of solar zenith angle made it possible to compare the plasma production via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…These densities are possibly due to transport via kinetic Alfvén waves during exposure to northward IMF, where the higher current density reveals the higher duskside magnetic field that also energizes faster (Walsh et al, 2014). Thus, while MHD simulations suggest that dawn-dusk asymmetry in solar wind entry by reconnection is related to ionospheric conductance (Li et al, 2008), the similarity between magnetized Earth's ionosphere and non-magnetized Mars's ionosphere (Burrell et al, 2020) makes it plausible that similar proportions of the dawn-dusk asymmetry should hold for Mars as well.…”
Section: Discussionmentioning
confidence: 99%
“…These densities are possibly due to transport via kinetic Alfvén waves during exposure to northward IMF, where the higher current density reveals the higher duskside magnetic field that also energizes faster (Walsh et al, 2014). Thus, while MHD simulations suggest that dawn-dusk asymmetry in solar wind entry by reconnection is related to ionospheric conductance (Li et al, 2008), the similarity between magnetized Earth's ionosphere and non-magnetized Mars's ionosphere (Burrell et al, 2020) makes it plausible that similar proportions of the dawn-dusk asymmetry should hold for Mars as well.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, recent work has suggested that the traditional approach of excluding time of day when considering Mars ionospheric variations with solar zenith angle may obscure important trends (Benna et al, 2015;Burrell et al, 2020;Cui et al, 2020;Gupta et al, 2021Gupta et al, , 2019Lee et al, 2020;Pilinski et al, 2019Pilinski et al, , 2017Steckiewicz et al, 2019). For instance, consider the dawn and dusk terminators.…”
Section: Datamentioning
confidence: 99%